2020
DOI: 10.3390/ijms21176099
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Combined Exercise Improves Inflammatory Profile in the Retina of Obese Mice

Abstract: Excess of adipose tissue increases the concentration of proinflammatory cytokines, triggering a subclinical inflammatory condition. This inflammatory profile contributes to retina damage, which can lead to retinal dysfunction and reduced vision. Regularly practicing both aerobic and strength exercises is well known for promoting anti-inflammatory effects on different organs in the peripheral and central regions. However, the effects of combined physical exercise (CPE; strength + aerobic) on the inflammatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Across 85 survey sites, they included 1909 participants in their investigation, and they found that DR was the second leading cause of blindness and visual impairment after cataracts. Blindness and moderate-tosevere visual impairment were high within the studied population for both conditions, and they cited many risk factors, which included physical inactivity[50]. Frith and Loprinzi et al (2018) investigated the impact of nonbouted, or lifestyle versus bouted, or structured form of physical activity on retinopathy prevalence and its severity among a selected cohort.…”
mentioning
confidence: 99%
“…Across 85 survey sites, they included 1909 participants in their investigation, and they found that DR was the second leading cause of blindness and visual impairment after cataracts. Blindness and moderate-tosevere visual impairment were high within the studied population for both conditions, and they cited many risk factors, which included physical inactivity[50]. Frith and Loprinzi et al (2018) investigated the impact of nonbouted, or lifestyle versus bouted, or structured form of physical activity on retinopathy prevalence and its severity among a selected cohort.…”
mentioning
confidence: 99%
“…There is a strong link between exercise and the inflammatory system in the human body including in the CNS (Nieman and Wentz, 2019). Exercise is known to modulate key inflammatory mechanisms, mitigating and regulating systemic inflammation in neurological diseases such as multiple sclerosis (Dalgas et al, 2012), systemic lupus erythematous (Perandini et al, 2012), Alzheimer's and Parkinson's diseases (Fuller et al, 2020), and preclinical models of retinal degeneration (Crowston et al, 2017;Sellers et al, 2019;Zhang et al, 2019;Dantis Pereira de Campos et al, 2020). However, these antineuroinflammatory effects, whilst observed, have not been wellsubstantiated or often investigated past single target identification.…”
Section: Exercise Induces Molecular Changes That Drive Towards a Heal...mentioning
confidence: 99%
“…To date, the majority of animal studies investigating the effect of exercise in the retina have used forced exercise models where an often unpleasant or painful stimulus is used to ensure the animals complete a defined amount of physical activity (Ji et al, 2013;Kim et al, 2013;Chrysostomou et al, 2014;Lawson et al, 2014;Chrysostomou et al, 2016;Allen et al, 2018;Mees et al, 2019;Dantis Pereira de Campos et al, 2020). While it is understandable that studies using forced-exercise models use this method in an attempt to ensure equal and consistent levels of desired exercise, output measures from our study revealed that mice would voluntarily and consistently utilize the running wheels, running large distances of 10.2 km/day on average, mitigating any need to force this seemingly natural behavior onto them.…”
Section: Voluntary Exercise Is Protective Against Retinal Degenerationmentioning
confidence: 99%
See 2 more Smart Citations